Caption as a Text to Promote Students’ Critical Thinking in Reading Comprehension of Senior High School (RETAIN, 2020)
Abstract Lately, caption text become the newest text in the 2013 curriculum. Caption text is defined as a short description used to describe an object or illustration from an image. Caption text must be informative because this would affect the implied meaning in an image (Grayam, 2010). In the 2013 curriculum, 12th-grade students in senior high school are expected to be able to understand the implied meaning of the caption text and be able to write the text according to a social function, text structure, and correct linguistic elements. In this case, reading and understanding the implicit meaning of a text requires critical thinking. Therefore, this phenomenological research aims to describe naturalistic phenomena related to the implementation of caption text as a text that can promote students' critical thinking in understanding the implied meaning of a caption, students' works, and students' responses in the teaching and learning process in class. The research subjects were 30 students and a teacher at MAN 2 Lamongan. The researcher observed the teaching and learning process in the classroom to describe the implementation of the caption text and how it can build students' critical thinking skills. The researcher also collected the students' works to describe the extent of their critical thinking skills in understanding the implied meaning of a caption text. Next, the researcher conducted interviews to describe students' responses during the teaching and learning process. Observation results showed that the implementation of caption text as text can promote the development of students' critical thinking in understanding caption text. The students' works showed that students can answer all questions beyond the picture well, especially in analyzing and evaluating a topic. Finally, the results of the interviews showed that teachers' methods and training succeeded in promoting their critical thinking in learning caption texts. Thus, teaching caption texts can promote students' critical thinking in understanding the implied meaning of the caption. Keywords: Reading comprehension, caption text, critical thinking